Fluorescence study of peptide and protein containing interpolyelectrolyte complexes - Mustafaev, M (WILEY-V C H VERLAG GMBH, 2004)
Four polyelectrolyte (PE)-protein and PE-peptide systems were selected for fluorescence experiments. The mode of binding of proteins to PE and structure of forming polycomplexes depends upon the ratio of components and chemical composition of polymer macromolecules. Complex formation of proteins with oppositely charged polycations is realized by the self-assembly of non-stoichiometric polycomplex particles with characteristic composition. These polycomplex particles have a rigid rod-like carcass structures in which protein molecules are practically exposed to the solvent. Two types of ternary polyanion-Cu2+-protein polycomplex particles are formed depending on the monomer composition of the copolymer. At higher content of hydrophobic N-isopropylacrylamide monomer unites, the protein globules in the structure of ternary polycomplex particles are densely covered by the shell of a polymer coil and practically fenced of from the water environment. At higher content of acrylic acid unites, polycomplex particles have more friable structures in which protein molecules are practically exposed to the solution. The PE-peptide conjugate species can be represented rather as a macromolecule of a segmented (block) copolymer in which the hydrophobic blocks, i.e. the sequences of copolymer and peptide unit pairs, which have formed the covalent and salt bonds alternate with hydrophilic ones, i.e. the sequences of the copolymer chain not participating in the formation of double strand blocks.
Keywords: bioengineering; covalent conjugates; fluorescence; peptides; polyelectrolytes; proteins; SERUM-ALBUMIN; ANTIBODIES; Polymer Science